A Study of Overreaction Hypothesis in the Indian Equity Market. (December 2014) - Choudhary, Kapil; Sethi, Naman
The purpose of this study is to examine the overreaction hypothesis in the Indian stock market during the period 1990 to 2012. It also explores whether this overreaction hypothesis is the manifestation of earlier anomalies such as size effect and value effect. The stock price and fundamental data of 1, 427 Indian firms listed on the Bombay Stock Exchange during the period 1990 to 2012 have been used. Time series regression and CAPM have been applied to test overreaction, size and value effects. The empirical results suggest that past losers have a tendency to outperform past winners for longer investment periods such as two to three years. Although lower in magnitude, yet this superior performance of loser stocks is economically significant in the Indian equity market. The empirical results do not reveal any calendar anomaly in the superior performance of loser stocks. Furthermore, the results indicate that losers tended to be small and value stocks and that the limited overreaction effects documented are probably attributable to the size and value effect in the Indian equity market during the last two decades. The findings may provide a base for investment managers and investors to reallocate their portfolio weights to small and value stocks. Earlier studies in the Indian context were primarily focused only on the overreaction hypothesis and to cover this research gap, a further dig has been made to uproot the possibility of size effect, value effect and seasonality in overreaction effects. A fairly large sample (1, 427 firms) has been used as compared to previous studies.